Axially loaded steel columns strengthened with CFRP - Kalavagunta S.; Naganathan S.; Mustapha K.N.B. (Jordan University of Science and Technology, 2023)
During the recent decades, Carbon Fiber-Reinforced Polymer (CFRP) composite materials have proven valuable properties and suitability to be used in the construction of new buildings and in upgrading the existing ones. The objective of this paper is to review the previous work in this area and compare it with the current experimental results to show the design equations for CFRP strengthened steel structural elements. Research findings have shown that CFRP sheets and strips are not only effective in restoring the lost capacity of a damaged steel section, but are also quite effective in strengthening of steel sections to resist higher loads, extend their fatigue life and reduce crack propagation. © 2014 JUST. All Rights Reserved.